Turbulent structure in supernova remnants G46.8−0.3 and G39.2−0.3 from THOR polarimetry - Shanahan, Russell; Stil, Jeroen M.; Anderson, Loren Dean; Beuther, Henrik; Goldsmith, Paul F.; Klessen, Ralf S.; Rugel, Michael; Soler, Juan D. (The astrophysical journal, 2023)
We present the continued analysis of polarization and Faraday rotation for the supernova remnants (SNRs) G46.8−0.3 and G39.2−0.3 in L-band (1-2 GHz) radio continuum in The H i/OH/Recombination line (THOR) survey. In this work, we present our investigation of Faraday depth fluctuations from angular scales comparable to the size of the SNRs down to scales less than our 16″ beam (≲0.7 pc) from Faraday dispersion (σ ϕ ). From THOR, we find median σ ϕ of 15.9 ± 3.2 rad m−2 for G46.8−0.3 and 17.6 ± 1.6 rad m−2 for G39.2−0.3. When comparing to polarization at 6 cm, we find evidence for σ ϕ ≳ 30 rad m−2 in localized regions where we detect no polarization in THOR. We combine Faraday depth dispersion with the rotation measure (RM) structure function (SF) and find evidence for a break in the SF on scales less than the THOR beam. We estimate the RM SF of the foreground interstellar medium using the SF of extragalactic radio sources and pulsars to find that the RM fluctuations we measure originate within the SNRs for all but the largest angular scales.